(untitled) (Research, Society and Development, 2022)
To describe the trend of physical disabilities caused by leprosy in children in the state of Tocantins. An analysis of the calculations of leprosy indicators and temporal trends was carried out in the period from 2001 to 2020. 1,983 new cases of leprosy were diagnosed in children under 15 years of age. Degree 2 of physical disability was more prevalent in males (66.67%). The prevalence of cases with grade 1 and 2 of physical disability was higher in the multibacillary classification, but the paucibacillary classification had a record of 31.56% of grade 1 and 17.95% of grade 2. The detection coefficient and the proportion of cases with grade 2 showed stability in the trend in the total period. Between 2014 and 2020, the proportion of paucibacillary cases had a significant reduction of 26.2%, while in the period 2014 and 2018, multibacillary cases had an increase of 38.2%. The proportion of grade 1 cases had a significant increase of 16.3% between 2001 and 2010 and of 58.7% between 2014 and 2018 and stability in the total period. Physical disabilities in children and adolescents remain an important public health problem at the time of leprosy diagnosis in the state of Tocantins. The trend towards stability in disability points to the persistence of endemic disease, late diagnosis, hidden prevalence and sequelae in children. Operational failures and failures in the clinical management of health services were clearly identified, which reaffirms the need to make more efforts to improve leprosy care.